Current trends in pediatric cardiac surgery and their impact on intensive care - Debasis Das; Shubhadeep Das (Journal of Pediatric Critical Care)
Recent advancements in pediatric cardiac surgery have significantly influenced the management of congenital heart disease (CHD) patients in intensive care units (ICUs). These developments include earlier surgical interventions, increasing complexity of procedures, and the rising prevalence of surgeries in neonates, premature infants, and low-birth-weight babies. Complex repairs, nonsternotomy approaches, such as minimally invasive surgeries and heart failure management with mechanical circulatory support, present unique challenges in postoperative care, including respiratory support, infection prevention, and management of low-cardiac output state (LCOS) and multiorgan dysfunction. In resource-limited settings, delayed presentations and fiscal constraints further complicate ICU management. Innovations such as protocol-based treatment, integration of artificial intelligence, and multidisciplinary collaboration are revolutionizing care strategies. This narrative review highlights the trends in pediatric cardiac surgery, their direct impact on ICU practices, and future directions aimed at improving survival rates, reducing complications, and enhancing the quality of care for CHD patients.